Student’s Difficulties and Their Overcoming Strategies in Comprehending Reading Section on TOEFL - Puspitaloka, Nina; Ardiyani, Mery; Anzani Putri, Nazma (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study aimed to investigate which skills were most difficult in the TOEFL Reading Comprehension section and to identify the strategies frequently used by students to overcome these difficulties within the English Language Education Study Program during the 2023 academic year at Universitas Singaperbangsa Karawang. This research employed a case study method, presented in a qualitative manner. The participants were third-semester students of the English Language Education Study Program enrolled in the Academic Reading course. Data collection techniques included classroom observation and questionnaires. Findings from the study indicated that the most difficult skill for students in the TOEFL Reading Comprehension section was Skill 6, which involves answering implied detail questions. This difficulty stemmed from the need to infer information not explicitly stated in the text, requiring a high level of concentration. Furthermore, the strategies students used to address these difficulties were based on Deborah Philips’ theory, which outlines five main strategies incorporating 13 specific skills that assist students in improving their understanding of text passages more effectively